Thymoquinone is a natural antibiofilm and pathogenicity attenuating agent in Pseudomonas aeruginosa - Al-Rabia, Mohammed W.; Asfour, Hani Z.; Alhakamy, Nabil A.; Abdulaal, Wesam H.; Ibrahim, Tarek S.; Abbas, Hisham A.; Salem, Ibrahim M.; Hegazy, Wael A. H.; Nazeih, Shaimaa I. (Frontiers in Cellular and Infection Microbiology, 2024)
Pseudomonas aeruginosa belongs to the critical pathogens that represent a global public health problem due to their high rate of resistance as listed by WHO. P. aeruginosa can result in many nosocomial infections especially in individuals with compromised immune systems. Attenuating virulence factors by interference with quorum sensing (QS) systems is a promising approach to treat P. aeruginosa resistant infections. Thymoquinone is a natural compound isolated from Nigella sativa (black seed) essential oil. In this study, the minimum inhibitory concentration of thymoquinone was detected followed by investigating the antibiofilm and anti-virulence activities of sub-inhibitory concentration of thymoquinone against P. aeruginosa PAO1. The effect of thymoquinone on the expression of QS genes was assessed by quantitative real-time PCR and the protective effect of thymoquinone against the pathogenesis of PAO1 in mice was detected by the mice survival test. Thymoquinone significantly inhibited biofilm, pyocyanin, protease activity and swarming motility. At the molecular level, thymoquinone markedly downregulated QS genes lasI, lasR, rhlI, and rhlR. Moreover, thymoquinone could protect mice from the pathologic effects of P. aeruginosa increasing mice survival from 20% to 100%. In conclusion, thymoquinone is a promising natural agent that can be used as an adjunct therapeutic agent with antibiotics to attenuate the pathogenicity of P. aeruginosa.